Identifying key factors for successful formulation and implementation of healthcare policies on non-communicable diseases: a multinational analysis - Babaita, Abdulfatai Olamilekan; Jahan, Yasmin; Nakamura, Ryota; Moriyama, Michiko (Frontiers in Public Health, 2024)
Objectives: Non-communicable diseases (NCDs) are a major public health concern that accounts for 74% of global deaths each year. The increasing burden of NCDs exhausts public health resources and threatens achievement of the 2030 agenda for sustainable development. The purpose of this study is to thematically analyze the contributory factors in the health policy process and reforms to strengthen the prevention of NCDs across borders; the milestones achieved through the process of policymaking, change, and implementation. Method: This paper informs and draws on the findings of contributory factors in the health policy process for the prevention of NCDs across borders: